전문용어 인식 시스템을 위한 분산 병렬 처리 플랫폼 최적화 및 성능평가 - 최윤수(Yunsoo Choi); 이원구(Wongoo Lee); 이민호(Minho Lee); 최동훈(Dong-Hoon Choi); 윤화묵(Hwamook Yoon); 송사광(Sa-kwang Song); 정한민(Hanmin Jung) (한국콘텐츠학회 논문지, 12(10), 2012)
Many statistical methods have been adapted for terminology recognition to improve its accuracy. However, since previous studies have been carried out in a single core or a single machine, they have difficulties in real-time analysing explosively increasing documents. In this study, the task where bottlenecks occur in the process of terminology recognition is classified into linguistic processing in the process of 'candidate terminology extraction' and collection of statistical information in the process of 'terminology weight assignment'. A terminology recognition system is implemented and experimented to address each task by means of the distributed parallel processing-based MapReduce. The experiments were performed in two ways; the first experiment result revealed that distributed parallel processing by means of 12 nodes improves processing speed by 11.27 times as compared to the case of using a single machine and the second experiment was carried out on 1) default environment, 2) multiple reducers, 3) combiner, and 4) the combination of 2)and 3), and the use of 3) showed the best performance. Our terminology recognition system contributes to speed up knowledge extraction of large scale science and technology documents. 과학기술 문헌의 전문용어 인식 분야는 지금까지 다양한 통계적 방법론을 사용하여 용어 인식 정확률을 향상시키기 위하여 연구되어 왔다. 하지만 기존의 연구는 단일-코어 또는 단일 머신 상에서 수행되었기 때문에, 폭발적으로 증가하는 문헌들에 대한 실시간 분석 요구를 처리할 수 없는 상황에 직면하고 있다. 본 논문에서는 전문용어를 인식하는 과정에서 병목현상이 발생하는 작업을 '후보용어 추출 과정'의 언어처리부분과 '용어 가중치 할당 과정'에서 통계정보를 취합하는 부분으로 분류하고, 각 작업을 분산병렬 처리 기반의 맵리듀스 작업을 이용하여 해결하는 전문용어 인식 방법을 구현하고 실험하였다. 실험은 확장성과 분산 병렬 처리 환경 최적화 두 가지로 수행하였고, 첫 번째 실험에서 12개의 노드를 사용하여 분산 병렬 처리하였을 때 단일 머신을 사용한 경우보다 11.27배의 처리속도 향상을 보였다. 두 번째 실험에서 1)기본 환경, 2)복수 리듀서, 3)컴바이너, 4) 2)와 3)의 조합에 대하여 수행하였고, 3)컴바이너 사용이 가장 우수한 성능을 보여 주었다. 본 논문에서 구현된 전문용어 인식 시스템은 대용량 과학기술 문헌에 대한 지식 추출 작업속도 개선에 기여하였다.